2021
DOI: 10.1002/ana.26052
|View full text |Cite
|
Sign up to set email alerts
|

Early Predictors of 9‐Year Disability in Pediatric Multiple Sclerosis

Abstract: The purpose of this study was to assess early predictors of 9-year disability in pediatric patients with multiple sclerosis. Methods: Clinical and magnetic resonance imaging (MRI) assessments of 123 pediatric patients with multiple sclerosis were obtained at disease onset and after 1 and 2 years. A 9-year clinical follow-up was also performed. Cox proportional hazard and multivariable regression models were used to assess independent predictors of time to first relapse and 9-year outcomes. Results: Time to fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 58 publications
1
23
1
Order By: Relevance
“…Availability of 3.0T scanners and improved spinal cord MRI acquisition allowed a better cord lesion detection, resulting in increased correlations with clinical measures 33. In line with this, recent studies reported a significant predictive role of cervical cord lesions on subsequent MS disease course 5 9…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Availability of 3.0T scanners and improved spinal cord MRI acquisition allowed a better cord lesion detection, resulting in increased correlations with clinical measures 33. In line with this, recent studies reported a significant predictive role of cervical cord lesions on subsequent MS disease course 5 9…”
Section: Discussionmentioning
confidence: 84%
“…In definite MS, T2-weighted5–8 and T1-weighted6 9 10 MRI brain abnormalities have been associated with more severe disability at medium-term and long-term follow-up 5–10. Conversely, only a few studies found that spinal cord lesions predicted long-term disability 5 9 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, POMS patients with the first demyelinating attack affecting the brainstem have a significantly greater risk for future disability progression (up to 5 times) when compared with patients with lesions in other CNS locations [ 27 ]. In a recent 9-year follow-up study, early treatment with high-efficacy medication resulted in a significantly longer time to a new relapse [ 28 ]. The presence of cerebellar lesions at baseline and high-efficacy medications was also associated with a lower long-term annualized relapse rate (ARR), whereas presentation of transverse myelitis was associated with a higher ARR over the follow-up [ 28 ].…”
Section: Disability Outcomes Predictors and Importance Of Treatment In Pomsmentioning
confidence: 99%
“…In a recent 9-year follow-up study, early treatment with high-efficacy medication resulted in a significantly longer time to a new relapse [ 28 ]. The presence of cerebellar lesions at baseline and high-efficacy medications was also associated with a lower long-term annualized relapse rate (ARR), whereas presentation of transverse myelitis was associated with a higher ARR over the follow-up [ 28 ]. In terms of long-term disability outcome, the occurrence of two new T2 hyperintensities and an EDSS increase within the first 2 years of the disease were able to predict 9-year disability worsening [ 28 ].…”
Section: Disability Outcomes Predictors and Importance Of Treatment In Pomsmentioning
confidence: 99%